2016
DOI: 10.20867/thm.22.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Responsible environmental behavior intention of travelers on ecotourism sites

Abstract: The purpose -This research aims to investigate responsible environmental behavior intention of travelers formed upon visiting ecotourism sites in Indonesia. Nowadays, ecotourism has become a popular concept of tourism in Indonesia due to its rich potential of natural and cultural resources. Nevertheless, it is undeniable that not all travelers visiting ecotourism objects demonstrate positive environmental behavior. Several previous studies have already revealed that travelers' behavior may alter after visiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…It is challenging for tourism enterprises to promote sustainable tourism and ecotourism because irresponsible visitor behaviors are seen everywhere [11]. Handriana and Ambara indicated that ecotourism or sustainable tourism should minimize natural and cultural environment destruction through people's environmentally responsible behaviors, and show respect for and return profits to local communities [12]. Based on previous research, tourism is often highly dependent on the natural and cultural environments of destinations.…”
Section: Sustainable Tourismmentioning
confidence: 99%
“…It is challenging for tourism enterprises to promote sustainable tourism and ecotourism because irresponsible visitor behaviors are seen everywhere [11]. Handriana and Ambara indicated that ecotourism or sustainable tourism should minimize natural and cultural environment destruction through people's environmentally responsible behaviors, and show respect for and return profits to local communities [12]. Based on previous research, tourism is often highly dependent on the natural and cultural environments of destinations.…”
Section: Sustainable Tourismmentioning
confidence: 99%
“…In addition to enjoying various attractions, they also need to get enlightenment about ecosystem education such as ways of conservation, various flora and fauna, and management system. More specifically, the notion of ecotourism as explained by The Ecotourism Society is a form of travel to natural areas that is performed with the aim of conserving the environment and preserving the lives and welfare of the local population (Handriana & Ambara, 2016). Thus, a tourist trip to the object of ecotourism must have a role in conserving nature while contributing to the prosperity of the community living around the area.…”
Section: Figurementioning
confidence: 99%
“…On the other hand, undoubtedly one of the main attractions that trigger tourism activity are natural resources, but the incessant increase in the flows of national and international tourists each year can lead to major changes in ecosystems (Si-Shyun, 2018). This can represent a high cost for the societies, cultures and host environments, due to the possible environmental destruction that would put their tourism heritage at risk which represents a cause of great concern for all sectors of the community (i.e., governments, professionals, local community, as well as a topic of interest to academics and researchers), who agree that in order for tourism to be maintained in a sustained manner, preventive or remedial measures should be considered to avoid a major negative impact (Briassoulis & Van Der, 2013;Tanti & Raya, 2016).…”
Section: Introductionmentioning
confidence: 99%